How misleading information interferes with child eyewitness identification : effect of lineup type and age in target absent trials - Caldeira, Johanne Lia Emonts (2015)
Existing literature on eyewitness testimony indicates that there is a wide range of variables which interfere with the reliability of eyewitness identifications (e.g., eyewitness’ age, target presence in the lineup, presence of misleading information and the entity that delivers it, lineup type). The present study focused on the efficency of simultaneous versus sequential lineups in children eyewitness testimonies in the case of target absent lineups, with the insertion of misleading information. The effect of children’s age was also investigated. Hence, 55 children of two different age groups (4-5 years-old and 8-10 years-old), divided into two lineup type conditions, viewed four videos of fake CCTV footage that depicted minor thefts. After a brief interference task, the children were asked to identify the suspect seen in the video, if they believed that he was amongst lineup members. Answers were registered according to the lineup member chosen, and could be of four different types: correct (no lineup member was chosen), dummy (the filler with the misinformation described features was chosen), pseudo-target (the filler with highest resemblance to the suspect in the video was chosen) and other (any of the other four lineup members was chosen). Results showed that younger children identify more frequently the dummy in the lineups than older children, evidencing a greater suggestibility. Additionally, results showed that participants identified significantly more “other” lineup members in the sequential lineup than in the simultaneous one, possibly because of not being able to exclude these members from their choice as easily as in the simultaneous lineup, which permits a relative judgment. This study has the potential to aid forensic investigations envolving child eyewitnesses, in an effort to understand and improve testimony and lineup methodology.